2017
DOI: 10.1016/j.jdent.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Confounding factors affecting the marginal quality of an intra-oral scan

Abstract: Title: Confounding Factors Affecting the Marginal Quality of an Intra-Oral ScanObjectives: To assess the effect of clinical factors on the quality of intra-oral scans of crown margins. These factors are; presence of adjacent teeth, proximity to gingivae, encumbrance of wand positioning within oral cavity. Methods:A typodont lower molar (Frasaco, Germany) was prepared for an all-ceramic crown with 1.5mm supraginigival (lingual) and equigingival (buccal) margins. The tooth was scanned in a model scanner, creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 14 publications
3
66
0
Order By: Relevance
“…Some researchers have reported that restoration type, tooth geometry, and tooth location affected the accuracy of digital impressions [21,27,28]. Proximal areas are most challenging for adequate digital impressions [21,29,30]. MO and DO cavities are commonly encountered in clinical practice, and have different accessibility and visual interference in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have reported that restoration type, tooth geometry, and tooth location affected the accuracy of digital impressions [21,27,28]. Proximal areas are most challenging for adequate digital impressions [21,29,30]. MO and DO cavities are commonly encountered in clinical practice, and have different accessibility and visual interference in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some in vitro studies on intraoral scanning were performed under free-space conditions, i.e., the model was held in the hand during scanning, which permitted greater freedom while placing the scanning wands [12][13][14][15][16][17][18][19]. A greater degree of freedom (than that which is actually available in the oral cavity) ensures a direct line-of-sight, favorable angle of incidence, which can affect the quality of the scan [30,31]. An in vivo study found that the precision for extraoral scanning was higher than that for intraoral scanning with the same intraoral scanner [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to adequately capture the dimensions of the peri‐implant soft tissues, the emergence profile should be cone‐shaped, and the depth of the implant platform should be less than 4 mm. A deeper implant platform could not be conveniently impressed, since working depth of the intraoral devices is limited, and the scanning field of view is restricted by the adjacent teeth …”
Section: Techniquesmentioning
confidence: 99%
“… 7 8 9 In this regard, the most commonly used scanners are extraoral and intraoral scanners. 10 11 12 13 14 15 Extraoral scanners to obtain three-dimensional (3D) data are laser, optical, white light, and blue light model scanners.…”
Section: Introductionmentioning
confidence: 99%